2023
DOI: 10.3390/en16237893
|View full text |Cite
|
Sign up to set email alerts
|

Passive Mixing and Convective Heat Transfer Enhancement for Nanofluid Flow across Corrugated Base Microchannels

Ali Ammar Naqvi,
Emad Uddin,
Muhammad Zia Ullah Khan

Abstract: Vortex generators and pin fins are conventionally used to deliver fluid mixing and improved convective heat transfer. The increased pressure loss following a fractional increase in heat transfer, as well as the complex manufacturing design, leave room for improvement. The present work proposes a novel diverging–converging base corrugation model coupled with vortex generation using simple geometrical modifications across rectangular microchannels to ensure a superior performance. The Nusselt number, friction fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Aluminium oxide [22][23], copper oxide [24], graphene oxide [25] and zirconia nanofluids [26] [27] have been studied to determine the superior cooling effects of nanofluids. Geometric modifications were applied by Naqvi et al to enhance the cooling rates and it was found that passive mixing combined with corrugation patterns provides increased cooling rates across cooling channels [28]. Li et al [29] found that increased pressure losses accompany the convective heat transfer enhancement from nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminium oxide [22][23], copper oxide [24], graphene oxide [25] and zirconia nanofluids [26] [27] have been studied to determine the superior cooling effects of nanofluids. Geometric modifications were applied by Naqvi et al to enhance the cooling rates and it was found that passive mixing combined with corrugation patterns provides increased cooling rates across cooling channels [28]. Li et al [29] found that increased pressure losses accompany the convective heat transfer enhancement from nanofluids.…”
Section: Introductionmentioning
confidence: 99%